Recursos TIC en el aprendizaje de la matemática de los estudiantes de quinto año de Educación General Básica de la Unidad Educativa “Adolfo Kolping”, cantón Riobamba, periodo 2023-2024 - Guamán Quishpe, Fabricio Miguel (2023)
The work objective of this study was to determine the TIC resources in the mathematics learning of students in the fifth year of General Basic Education of the "Adolfo Kolping" Educational Unit. The methodology was qualitative; the research design was characterized by a non-experimental design, using a descriptive and field research type. The type of study was also cross-sectional. We worked with a population of 316 students, of which a non-probabilistic intentional sampling was used to select the sample at the researcher's discretion; the sample consisted of 30 students of the 5th year of EGB and a teacher of the same grade. The data collection technique is direct observation and unstructured interview whose instrument is the observation form for the students and the interview guide for the teacher, which allowed to establish the respective conclusions and recommendations which at the end of the interview were as follows the following results were determined; students who used TIC resources in learning mathematics strengthen their significant knowledge, while children who do not use TIC resources do not harden their learning, therefore, it is essential that TIC resources are a fundamental part in the teaching of students in the educational establishment "Adolfo Kolping" because the institution does not use or have the necessary ICT resources to teach more interactive mathematics classes, therefore, a guide to ICT resources in learning is proposed, which aims to help students and teachers with a wide variety of ICT resources for learning mathematics and use them effectively in their daily and professional life.